1980
DOI: 10.1056/nejm198012043032302
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the Bleeding Tendency in Uremia with Cryoprecipitate

Abstract: We gave cryoprecipitate to six patients with uremia and bleeding times prolonged to more than 15 minutes. After the infusion, all patients had shortened bleeding times; the times of five became normal. In four patients control of major bleeding episodes was attained, and five underwent major surgical or invasive procedures, with good hemostasis. After infusion the time before the nadir of the bleeding time was reached was between one and 12 hours. The bleeding time returned to pretreatment levels by 24 hours a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
3

Year Published

1982
1982
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(71 citation statements)
references
References 17 publications
2
65
0
3
Order By: Relevance
“…In patients with vascular diseases or denudation of the endothelium and exposed subendothelium (e.g. in myocardial infarction, acute respiratory failure, acute and chronic renal insufficiency, hypertension, diabetic nephropathy, vasculitis) [5, 28, 29, 30, 31, 32, 33]vWf is regarded as a marker of endothelial dysfunction [34]. …”
Section: Discussionmentioning
confidence: 99%
“…In patients with vascular diseases or denudation of the endothelium and exposed subendothelium (e.g. in myocardial infarction, acute respiratory failure, acute and chronic renal insufficiency, hypertension, diabetic nephropathy, vasculitis) [5, 28, 29, 30, 31, 32, 33]vWf is regarded as a marker of endothelial dysfunction [34]. …”
Section: Discussionmentioning
confidence: 99%
“…8 Subsequently, several investigators found that vWF was high in an array of clinical situations, all characterized by vascular damage with denudation of the endothelium and exposure of the subendothelium (for instance, acute respiratory failure, acute and chronic renal insufficiency, hypertension, diabetic nephropathy, and vasculitis). [23][24][25][26][27][28][29] To interpret these findings, it has been postulated that in patients with large-and small-vessel disease, the membranes of damaged endothelial cells would "leak" vWF, leading to an increase of the plasma levels of this protein. Clinicians became attracted by this simple approach to the evaluation of the degree of endothelial damage in vascular disease, because it reminded them of the usefulness and widespread adoption in clinical practice of the measurement of serum enzymes to evaluate the degree of hepatic and cardiac cell damage.…”
Section: Vwf: a Marker Of Endothelial Damage?mentioning
confidence: 99%
“…The risk of arteriovenous fistulae, hemorrhage and hematuria [7,8,31] have all been positively corre lated with blood pressure elevation. The year of biopsy, use of fluoroscopy or the presence of systemic disease [48]. However, patients with the clinical presentation of end-stage renal disease often have little to gain from a kidney biopsy.…”
Section: Risk Factorsmentioning
confidence: 99%